Intervensi untuk Mengurangi Academic Anxiety pada Mahasiswa Rumpun Kesehatan: Scoping Review - Hernanda, Messayu Fathasari (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Academic and emotional demands on healthcare students can cause mental health problems, one of which is academic anxiety. Academic anxiety is one type of anxiety that comes from the ongoing educational process. Academic anxiety experienced by health students can affect their academic achievement. Thus, various interventions are needed to overcome the impact of academic anxiety. This study aimed to map out the interventions used to reduce academic anxiety. This research method is a scoping review with PRISMA-ScR guidelines. The literature search was conducted using the PubMed, CINAHL & Springerlink databases, and the Google Scolar&ProQuest search engine. The year range of the article is the last 10 years. The keywords used were "Students in the health cluster," "Academic anxiety," and "Intervention". The screening was carried out used PRISMA Flow diagram and assessed by JBI. Found 14 articles discuss about non-pharmacological interventions that can reduced academic anxiety in healthcare students, that are progressive muscle relaxation, music therapy, mindfulness, aromatherapy, the use of nutmeg seeds, animal-assisted therapy, auricular stimulation vs expressive writing and support, efforts, and self-efficacy. To reduce academic anxiety in healthcare students, appropriate interventions are needed. The given intervention is expected to reduce the level of academic anxiety and can improve learning achievement in healthcare students. Keywords: Academic Anxiety, Health Science Student, Intervention  ABSTRAK Tuntutan secara akademik maupun emosional pada mahasiswa rumpun kesehatan dapat menyebabkan masalah kesehatan mental, salah satunya kecemasan akademik. Kecemasan akademik merupakan salah satu jenis kecemasan yang datang dari proses akademik berlangsung. Kecemasan akademik yang dialami oleh mahasiswa kesehatan dapat memengaruhi prestasi akademiknya. Sehingga, diperlukan berbagai macam intervensi untuk mengatasi dampak dari kecemasan akademik. Tujuan penelitian ini yaitu memetakan intervensi yang digunakan untuk mengurangi kecemasan akademik. Metode penelitian ini berupa scoping review dengan pedoman PRISMA-ScR. Pencarian literature dilakukan menggunakan database PubMed, CINAHL & Springerlink dan mesin pencarian Google Scolar&ProQuest. Rentang tahun artikel 10 tahun terakhir. Kata Kunci yang digunakan yaitu “Mahasiswa rumpun kesehatan”, “Kecemasan akademik”, “Intervensi”. Skrining dilakukan menggunkan PRISMA Flow diagram dan dinilai dengan JBI. Ditemukan 14 artikel yang membahas mengenai intervensi non farmakologi yang dapat digunakan untuk mengurangi kecemasan akademik pada mahasiswa rumpun kesehatan yaitu progressive muscle relaxation, music therapy, mindfulnes, aromaterapi, penggunaan biji buah pala, animal assissted therapi, auricular stimulation vs expressive writing dan dukungan, upaya, serta efikasi diri. Untuk mengurangi tingkat kecemasan akademik pada mahasiswa rumpun kesehatan diperlukan intervensi yang sesuai. Intervensi yang diberikan diharapkan dapat mengurangi tingkat kecemasan akademik dan dapat meningkatkan prestasi belajar pada mahasiswa rumpun kesehatan. Kata Kunci: Intervensi, Kecemasan Akademik, Mahasiswa Rumpun Kesehatan